ANALISIS KRIMINOLOGIS TERHADAP PERJUDIAN BOLA GULING DI PASAR MINGGUAN RAJA DAN BOAWAE KABUPATEN NAGEKEO PROVINSI NUSA TENGGARA TIMUR - Lepe, Salmania; Amalo, Heryanto; Fallo, Debi F. Ng (Petitum Law Journal, 2025)
This study examines the criminological factors underlying the high activity of rolling ball gambling in Pasar Mingguan Raja and Boawae, Nagekeo Regency, NTT. Qualitative empirical methods were applied through observation, interviews, and document analysis. The research findings revealed six contributing factors: (1) economic pressures such as poverty and unemployment; (2) market culture that makes gambling a common form of entertainment; (3) weak implementation of religious values; (4) lack of supervision and law enforcement due to limited human resources and geographical conditions; (5) low levels of education and legal awareness in society; and (6) the influence of a permissive environment (differential association). The countermeasures taken by the Boawae Police, such as counseling, patrols, raids, cooperation with community and religious leaders, and enforcement of Article 303 of the Criminal Code, have not achieved maximum results due to location mobility constraints, the existence of an early warning system from the perpetrators, low levels of community participation, and limited resources. In conclusion, an integrated holistic approach is needed, including consistent law enforcement, strengthening the economy, education, and revitalizing cultural and religious values.